Il modello corporeo: un’indagine sulla normatività dell’incorporamento di dispositivi biosintetici - Properzi, Martina (Filosofia Morale/Moral Philosophy, 2022)
In the contemporary intersectorial science of human embodiment, the concept of body model refers to an internal description of the anatomical, volumetric and structural properties of human corporality. It has been demonstrated that the body model plays a normative role in shaping a pre-reflective sense of body ownership, which is centrally involved in the lived experience of incorporating medical devices, such as prostheses and implants. However, further investigation is required to understand the normativity exercised by the body model with regard to a new generation of bio-integrated medical devices known as biosynthetic devises. The main objective of this essay is to clarify the normative role of the body model in the incorporation of biosynthetic devices. My starting point is an interdisciplinary methodology inspired by that developed by representatives of the postphenomenological movement.